THE EFFECTS OF FOREIGN DIRECT INVESTMENT AND PROFITABILITY ON THE STOCK RETURNS - Metyopandi, Vierkury; Salim, Ubud; Aisjah, Siti (Universitas Brawijaya, Indonesia, 2023)
This research aimed to identify how to examine and analyze the effects of foreign direct investment and profitability on the stock returns in manufacturing companies registered on IDX during 2016-2018. The total population was 91 companies registered and filtered into 32 registered companies according to the sample criteria and analyzed through Eviews 10 software. The research result referred that the foreign direct investment received by multinational companies could not yet affect stock return directly. Also, foreign direct investment was not able to influence the return on asset (ROA), but it was able to affect the return on equity (ROE). Further, ROA was not able to affect the increase of stock returns, while ROE was able to affect the rise of stock returns. Another research finding showed that ROE was the only one that could be a mediation variable in the relationship between foreign direct investment affecting stock returns. At the same time, ROA could not be a mediation variable. For the next studies, the researchers suggested exploring the other financial performance variables suited to foreign direct investment to affect the stock returns. In practice implication from this research, the investors must see how strong the capital owned by a company that accepts foreign direct investment and the relation, how the capital they receive can improve or maintain the company's financial performance within a certain period of time.